2016 AIChE Spring Meeting & 12th Global Congress on Process Safety : 50th Annual Loss Prevention Symposium (LPS) (Center for Chemical Process Safety/AIChE, 2016)
This conference will be the 50th Anniversary of the Loss Prevention Symposium (LPS). LPS is one of four parallel symposia that comprise The Global Congress on Process Safety (GCPS). The purpose of the LPS conference is to aid in the prevention of serious loss incidents that involve fires, explosions, runaway reactions, and major material releases in the chemical, petrochemical, and related industries. The conference agenda will consist of eleven sessions, each with three 25-minute presentations. Papers are selected by session chairs based on an abstract of 100-200 words. The abstract must offer a brief account of the contents, conclusions, and the relevance to the topic area. Submitted abstracts must include the author, their affiliation, full address, email, and phone number. The papers will be published in the GCPS proceedings. Abstracts will need to be submitted online, by October 15, 2015.
Prepared for Presentation at American Institute of Chemical Engineers 2016 Spring Meeting 12th Global Congress on Process Safety Houston, Texas April 11-23, 2016.
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books